Back Cover. Issue 7 (1st March 2022) - Unknown
Abstract : This cover picture displays porous assembly of metallo‐triangle [Zn3 LA3 ] 6+ and octahedron polyoxometalate [Mo6 O19 ] 2– via ionic complexation. The obtained composites exhibit precise 3D network structures with ideal stability containing micropores. Moreover, they show differential vapor adsorption behaviors for benzene, toluene, and cyclohexane. More details are discussed in the article by Wang et al . on page 813—818. Abstract : This cover picture displays porous assembly of metallo‐triangle [Zn3 LA3 ] 6+ and octahedron polyoxometalate [Mo6 O19 ] 2– via ionic complexation. The obtained composites exhibit precise 3D network structures with ideal stability containing micropores. Moreover, they show differential vapor adsorption behaviors for benzene, toluene, and cyclohexane. More details are discussed in the article by Wang et al . on page 813—818.